Characterization of Side Emitting Polymeric Optical Fibres (Journal of Fiber Bioengineering and Informatics, 2012)
The main aim is evaluation of illumination intensity for side emitting plastic optical fibres in dependenceon the distance from light source. The special device for measurement of light intensity on surface andcross section at various distances from light source is described. The dependence of surface and crosssection light intensity on the distance from light source is expressed by the exponential type model withtwo parameters; it is illumination intensity in the input into fibre and fibre attenuation factor. Fortextile structures with optical fibres the illumination intensity is evaluated as well. It was found thatillumination intensity of textile structures is very different. It is dependent on the trajectory of opticalfibre in textile structure. The highest illumination intensity is for straight fibre in textile with lowerwaviness.
Keywords: Polymer Optical Fibres; Side Emitting; Attenuation Factor; Light Intensity